MODAL SOSIAL MASYARAKAT KORBAN DALAM KONTEKS KEBIJAKAN PEMBEBASAN TANAH PROYEK BANJIR KANAL TIMUR (BKT) DI DKI JAKARTA - Pieter George Manoppo (JMBA Jurnal Manajemen dan Bisnis, 2015)
The objective of this research is to find out how the impact of land acquisition policy for the East Flood Canal (BKT) project against social capital from community victims in DKI Jakarta. This research used the qualitative approach with descriptive-phenomenology method. The data were obtained by in-depth interview, focus groups discussions, study of document and observation. Results of the study prove that impact of land acquisition policy for BKT project against social capital from community victims (land owners), occurred in two strategic environment. First, the destruction occurred in the internal environment of social capital, covered the category of structural, relational and cognitive capital, includes the all of its factual dimensions; Second, the onset of reproductive process of destruction on the environment around social capital through the action of human rights violations, presenting the potential for violence conflict, prolonged psychosocial trauma, and disintegration of the city land used. Destruction of social capital from community victims was proven to be rooted in typology of the land acquisition policy on BKT project: a) focusing on the BKT Value Offers Tax Object (NJOP) as the basic for the calculation, b) characterizing the dominance of government power and repressive action. According on the research finding, can be concluded that the land acquisition policy for BKT project, based on NJOP calculation, proven destructive impact, both social capital destruction and then reproduction of social capital destruction process on community victims systematically.